Longitudinal Sodium MRI of Multiple Sclerosis Lesions: Is there Added Value of Sodium Inversion Recovery MRI. Issue 1 (14th July 2021) - Mennecke, Angelika B.; Nagel, Armin M.; Huhn, Konstantin; Linker, Ralf A.; Schmidt, Manuel; Rothhammer, Veit; Wilferth, Tobias; Linz, Peter; Wegmann, Julius; Eisenhut, Felix; Engelhorn, Tobias; Doerfler, Arnd
Abstract : Background: Sodium enhancement has been demonstrated in multiple sclerosis (MS) lesions. Purpose: To investigate sodium MRI with and without an inversion recovery pulse in acute MS lesions in an MS relapse and during recovery. Study Type: Prospective. Subjects: Twenty‐nine relapsing–remitting MS patients with an acute relapse were included. Field Strength/Sequence: A 3D density‐adapted radial sodium sequence at 3 T using a dual‐tuned ( 23 Na/ 1 H) head coil. Assessment: Full‐brain images of the tissue sodium concentration (TSC1, n  = 29) and a sodium inversion recovery sequence (SIR1, n  = 20) at the beginning of the anti‐inflammatory therapy and on medium‐term follow‐up visits (days 27–99, n  = 12 [TSC], n  = 5 [SIR]) were measured. Regions of interest (RoIs) with contrast enhancement (T1 CE+) and without change in T1‐weighted imaging (FL + T1n) were normalized (nTSC and nSIR). To gain insight on the origin of the TSC enhancement at time point 1, it is investigated whether the nTSC enhancement of the lesions is accompanied by a change of the respective nSIR. Potential prognostic value of nSIR1 is examined referring to the nTSC progression. Statistical Tests: nTSC and nSIR were compared regarding the type of lesion and the time point using a one‐way ANOVA. Pearson's correlation coefficient was calculated for nTSC over nSIR and for nTSC1‐nTSC2 over nSIR1. A P ‐value <0.05 was considered statistically significant. Results: At the first measurement, all lesion types showed increased nTSC, while nSIR was decreased in the FL + T1 n and the T1 CE+ lesions in comparison to the normal‐appearing white matter. For acute lesions, the difference between nTSC at baseline and nTSC at time point 2 showed a significant correlation with the baseline nSIR. Data Conclusion: At time point 1, nTSC is increased, while nSIR is unchanged or decreased in the lesions. The mean sodium IR signal at baseline correlates with recovery or progression of an acute lesion. Evidence Level: 2 Technical Efficacy: Stage 4